Effect of Principal’s Leadership Style and Motivation toward Teacher’s Performance - Salimin Salimin; Happy Fitria; Destiniar Destiniar (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
This study determined the effect of principal’s leadership style and motivation on the performance of Public Elementary School teachers in Babat Toman District. This research used a quantitative method with the type of correlational research. The study population was 160 people. The sample was 80 people. The sampling technique in this study used a purposive sampling method. Data collection technique was using a questionnaire. Data were analyzed using correlation analysis and multiple regression techniques. The results showed that (1) the principal's leadership style had a positive and significant effect on the teacher’s performance at the State Elementary School in Babat Toman; (2) motivation has a positive and significant effect on the teacher’s performance; and (3) the principal's leadership style and motivation together have a positive and significant effect on the teacher’s performance of Public Elementary Schools in Babat Toman.